Abdominal Sepsis in Surgery and does this "Diagnosis" Really Exist? Effective Surgical Therapy - Hernández, José Luis García; Sánchez, Morelos Adolfo García; Barrón, Gema Méndez; Suárez, Ivonne Alondra León; Cabello, José de Jesús Urbina (British Journal of Healthcare and Medical Research, 2025)
Introduction: the medical area presents an accelerated advance in knowledge, as well as in technology, which has caused empty gaps that confuse, transcend and are filled or transformed into fiction or unfounded criteria; the specialty of Surgery tends to this phenomenon. Objective: 7 years of experience in the treatment of patients with abdominal sepsis in 3 hospitals. Method: a multicenter, retrospective, longitudinal, observational and descriptive study was conducted to review the records of patients surgically treated for abdominal sepsis over a period of 7 years. Results: 353 patients with abdominal sepsis treated surgically; 243 men (69%), 110 women (31%), with an age range of 18 to 81, mean 42; the first cause is biliary pathology, in 22.94% it does not start with an infectious process, diabetes mellitus occupies the 1st place as comorbidity 39%. Morbidity of 79% and mortality of 23.51%. Discussion: most deaths are caused by the "host response to the infection itself", it is not supported by evidence; this not only skews the science used to model it, but also the approaches to treat it, the accurate diagnosis of infectious diseases is a complex process influenced by factors such as clinical judgment, diagnostic methods and the availability of resources. Conclusions: abdominal sepsis (infectious) does not exist as a real diagnosis, but is an inflammatory process of the individual, complex, multifactorial, where incorrect diagnosis and treatment impact the patient's life. In Mexico, a real situational diagnosis of the health sector must be carried out and a reengineering of processes in the quality of medical-surgical, administrative and research care must be carried out to initiate a beneficial/correct, efficient, effective change in mortality erroneously called abdominal sepsis.